A PRAGMATIC REPRESENTATION OF RACISM IN PRESIDENT TRUMP'S TWEETS AND SPEECHES - Asst. Prof. Nesaem Mehdi Al-Aadili (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study is an attempt to pragmatically reveal how racist ideology is expressed and represented in discourse. American discourse is purposefully chosen as the data of the current study because racism was and still is a prime might behind segregation in the US. In other words, the study analyzes the pragmatic strategies used by the current President of the US, Donald Trump, in his racist speeches and tweets. Although Trump says that "he is the least racist person anywhere in the world", he has, in fact, many racist beliefs and actions and he is always accused, even by his employees, of fueling.